2022
DOI: 10.1371/journal.pone.0272444
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Kangaroo Mother Care at a tertiary level hospital in Zambia: A prospective descriptive study

Abstract: Background Globally, complications due to preterm birth are the leading contributor to neonatal mortality, resulting in an estimated one million deaths annually. Kangaroo Mother Care (KMC) has been endorsed by the World Health Organisation as a low cost, safe, and effective intervention in reducing morbidity and mortality among preterm infants. The objective of this study was to describe the implementation of a KMC model among preterm infants and its impact on neonatal outcomes at a tertiary level hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Bene ts of SSC SSC has been shown to have positive effects on both infants and mothers including lowering infant mortality rates, easing the transition to extrauterine [20], promoting thermoregulation and early hemodynamic stability even in premature babies, promoting metabolic balance and optimal neurological development, decreasing the incidence of postpartum depression, reducing infant crying, improving mother and infant bonding [21,22]. One of the most studied bene ts of SSC is its impact on breastfeeding, which is a crucial practice for maternal and child health [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Bene ts of SSC SSC has been shown to have positive effects on both infants and mothers including lowering infant mortality rates, easing the transition to extrauterine [20], promoting thermoregulation and early hemodynamic stability even in premature babies, promoting metabolic balance and optimal neurological development, decreasing the incidence of postpartum depression, reducing infant crying, improving mother and infant bonding [21,22]. One of the most studied bene ts of SSC is its impact on breastfeeding, which is a crucial practice for maternal and child health [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…KNH could consider implementing suggestions from the mothers as a recent study done in Zambia revealed that improvement in the setting of a number of KMC rooms improved infant outcomes. 28 Another theme that emerged was the need for appropriate KMC clothing. This observation is also consistent with other studies that have highlighted the importance of providing appropriate clothing for mothers practicing KMC 23 as well as a comfortable environment.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is also consistent with other studies that have highlighted the importance of providing appropriate clothing for mothers practicing KMC 23 as well as a comfortable environment. 28 Inadequate clothing can make it difficult for mothers to practice KMC effectively and comfortably, which can negatively impact the health of the preterm baby.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also revealed a significant association between nurse’s knowledge, attitude/beliefs, education about SSC, and nurses’ perceptions towards SSC implementation in a tertiary hospital SSC knowledge, attitudes, and belief; SSC education; SSC implementation Fatma et al 2022 [ 29 ] A quasi-experimental design Egypt The aim was to evaluate the effect of a kangaroo care educational program for mothers on weight gain of premature neonates in neonatal intensive care units Purposive sampling of 50 mothers of preterm infants 88% of mothers in the study had an unsatisfactory level of knowledge in the pre-educational program, while 96% of them had a satisfactory level of knowledge in the post-educational program. 64% of the mothers had incompetent practices in the pre-educational implementation, while 58% of them had competent practices in the post-educational program implementation Identify the importance of KMC Apply KMC steps Apply daily routine care (umbilical cord care) Muttau et al 2022 [ 30 ] Prospective descriptive study, using qualitative and quantitative methods Zambia The aim of the study was to describe the implementation of a KMC model among preterm infants and its impact on neonatal outcomes at a tertiary hospital in Lusaka, Zambia None A total of 573 neonates were enrolled into the study. 13 extremely low-weight preterm infants who were admitted to the KMC room graduated to Group A (1000 g-1499 g with a median weight gain of 500 g. Of the 419 very-low-weight neonates, 290 remained in Group A, while 129 improved to Group B (1500 g-24999 g) with a median weight gain of 280 g. Of the remaining 89 low-weight neonates, one regressed to Group A, while 77 remained in Group B, and 11 improved to group C (> 2500 g) with a median weight gain of 100 g Benefits of KMC; Appropriate KMC techniques; Position of newborn during breastfeeding; Importance of practicing good hygiene; Individual support Habte et al 2023 [ 31 ] Cross-sectional study Southern Ethopia The aim of the study was to assess the compliance of postnatal mothers toward World Health Organization-recommended elements of KMC in Southern Ethopia Mothers who gave birth to preterm or low-birth-weight infants were purposively sampled, using a single population proportion formula with a margin error of 5% and a 95% confidence interval The mean practice score of KMC item was 5.12 with 2 and 10 as the minimum and maximum item scores.…”
Section: Steps Of Integrative Literature Reviewmentioning
confidence: 99%